Water quality and waste management - Wan Johari, Wan Lutfi (Universiti Putra Malaysia Press, 2013)
This book encompasses the distribution and treatment of water quality, and solid waste treatment, control, modelling and management. It touches on a variety of many branches of environmental sciences including aspects of chemistry, biology and statistics, to name only a few. It aims to understand pollution of air, water and soil, and their control technologies in Malaysia. Water quality refers to the measures of physical, chemical, and biological aspects of water in relative to the needs of human or the environment. The first part of this book explores the quality of both surface and ground waters in Malaysia in terms of distribution, chemistry, pollution source and treatment. Statistical methods are mainly utilized to investigate and identify various relationships based on multiple water quality parameters. The second part of this book covers relevant information on waste management. Surveys were conducted and production of wastes was predicted using modeling approach.